UX Trek: A post-interaction journey from immersive experience logs - Marques, Leonardo; Amazonas, Mauro; Assunção, Willian; Castro, Thaís; Zaina, Luciana; Gadelha, Brundo; Conte, Tayana (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
User Experience (UX) is a holistic attribute focused on the quality of user-product interaction. However, the technology evolution in different contexts has not imposed limits on userproduct interactions. For instance, in immersive technologies, the goal is to create a sense of immersion for the user, to the point that the boundaries between the physical and virtual worlds are blurred. There are entertainment applications for large events in that context, whose goal is to transform the audience’s role from a mere spectator to an active element of the show. Thus, one of UX’s most important dimensions in this context is user engagement (UE). In this work, we propose two metrics to investigate engagement through the automated analysis of logs, which are records that contain the data of the users’ immersive interaction. We carried out two studies with two applications that actively engage the user in different experiences. The results showed the feasibility of using the metrics in log files, enabling both the automatic evaluation of UX and engagement understanding